ANALYSIS OF METHODS FOR ASSESSING THE IMPACT OF A COKE PLANT ON THE ENVIRONMENT - Galkina, O.; Kunytskyi, S.; Ivanchuk, N.; Tkachov, V.; Kunytskyi, M. (Municipal economy of cities. Series: «Economy science», 2023)
This academic paper explores various assessment methods used to evaluate the environmental impact of industrial enterprises, specifically focusing on coke plants. The study emphasises the widespread use of a global risk-based approach for assessing the environmental risks posed by such enterprises to both the environment and public health. This approach involves predicting potential future environmental consequences under different scenarios, with the choice of a specific method dependent on the particular conditions, objectives, and available resources.The analysis of these assessment methods reveals the prevalence of an integrated approach, which comprehensively evaluates multiple aspects of an industrial enterprise’s environmental impact. Moreover, the research underscores the importance of adopting modern technologies and strategies to enhance water supply and wastewater management efficiency for environmental preservation.The assessment of the ‘Kharkiv Coke Plant’ indicates minimal impact on land inundation issues, with little effect on groundwater quality. However, the excessive consumption of freshwater remains a significant concern, necessitating improved efficiency in the operation of the plant’s wastewater recycling systems. To evaluate the enterprise’s influence on surface waters, notably the Lopan and Udy rivers, the paper calculates the volume and flow of wastewater originating from the facility’s premises.Additionally, environmental impact assessment is conducted using key environmental indicators, including the alarm index, hazard index, and priority index. In light of the identified environmental challenges at the investigated industrial facility, including wastewater discharge into the municipal sewerage system, high water consumption, and phenol emissions from the quenching tower, the paper proposes a solution. This solution entails enhancing the plant’s water recycling infrastructure through the implementation of a closed-loop water recycling system and improving the efficiency of the biochemical plant. This approach aims to mitigate the environmental impact of the enterprise while promoting sustainable water management practices.